Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data - Luo, Yanping; Jiang, Jian; Wang, Lili; Shu, Zufei; Tong, Xiaoli (Zootaxa, 2020)
Vietnamella chebalingensis Tong, sp. nov. is described based on larval stage from China. The new species is distinguished from its congeners by the following combination of characters: body purple black with mottled white markings; length of inner pairs of cephalic projection approximately half of the outer pairs; posterior margin of abdominal tergites I–VI and VIII–X each with a pair of pointed projections, but tergite VII bearing only a single projection. The morphological evidence and molecular data (COI, Kimura 2-parameter) support that this new species represents the sixth species of the genus Vietnamella. An identification key to known larvae of the genus Vietnamella is provided.